High Blood Pressure: What You Need to Know - Linda B. Bobroff (EDIS)
High blood pressure, also called hypertension, increases your health risks. If you have high blood pressure, you have a higher chance of developing heart or kidney disease or having a stroke. This 4-page fact sheet discusses medical problems associated with untreated high blood pressure, risk factors, risk reduction, causes, and prevention. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, revised October 2016.